TiO2 / GPE / MWCNTs super-hydrophobic durable anti-icing coating as well as preparation method and application thereof

By applying TiO2/GPE/MWCNTs super hydrophobic and durable anti-ice coating on wind turbine blades, the problem of wind turbine blades is solved, and the all-weather anti-ice deicing adaptability and efficient deicing effect are achieved. Reduced deicing costs.

CN119410210AInactive Publication Date: 2025-02-11ZHONGDIAN HUACHUANG ELECTRIC POWER TECH RES +1

Patent Information

Application Number
CN202510006143.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Wind generator blades are prone to freezing in coastal and high altitude areas, resulting in unstable operation and reduced power generation efficiency. The existing deicing technology has problems such as high energy consumption, labor-intensiveness and high cost.

Method used

Using TiO2/GPE/MWCNTs super hydrophobic and durable anti-ice coating, the coating consists of graphene, multi-wall carbon nanotubes, hydrophobic titanium dioxide and binder. It is prepared by one-step spraying technology and has excellent electric and photothermal removal. Ice effect.

Benefits of technology

The wind turbine blades are all-weather anti-icing and deicing adaptability is achieved. The ice has low adhesion strength to the coating. The coating has efficient self-cleaning ability and good durability, which reduces the deicing cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410210A_ABST
    Figure CN119410210A_ABST
Patent Text Reader

Abstract

The invention discloses a TiO2 / GPE / MWCNTs super-hydrophobic durable anti-icing coating and a preparation method and application thereof, and belongs to the technical field of anti-icing surface engineering.The TiO2 / GPE / MWCNTs super-hydrophobic durable anti-icing coating is prepared from graphene, multi-walled carbon nanotubes, hydrophobic titanium dioxide and a binder; wherein the mass ratio of the graphene to the multi-walled carbon nanotubes is 1: 2, and then uniformly mixing the raw materials to obtain a target solution; and spraying the target solution onto a substrate by adopting one-step spraying, and drying to obtain the super-hydrophobic durable anti-icing coating. The super-hydrophobic durable anti-icing coating obtained through the preparation method can be based on photo-thermal and electric heating, is used for meeting the all-weather anti-icing and deicing adaptability of the wind driven generator fan blade, and has low adhesion strength of ice to the coating; and one-step spraying is adopted, so that the technological process is remarkably simplified, and the cost and the energy consumption are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of anti-icing surface engineering, and in particular relates to a TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating, and a preparation method and application thereof. Background Art

[0002] With the gradual depletion of traditional fossil fuels, wind power generation has become a clean, renewable, and large-scale economical way of power generation. In order to make full use of wind energy, wind turbines are usually installed in coastal areas and high-altitude mountainous areas. In these areas, icing on the surface of wind turbine blades is inevitable, which seriously threatens the reliability of wind turbine operation and power generation efficiency. Therefore, solving the problem of icing on wind turbine blades has become the key to ensuring the safe and stable operation of wind turbines. At present, the main deicing strategies are mechanical deicing, thermal deicing, and ultrasonic deicing. However, these traditional deicing technologies have their disadvantages, including high energy consumption, labor-intensive time requirements, and expensive costs.

[0003] Therefore, there is an urgent need to provide a super-hydrophobic composite anti-icing coating based on the combination of photothermal and electrothermal to meet the adaptability of wind turbine fan blades for all-weather anti-icing and deicing. Summary of the invention

[0004] In order to overcome the above technical problems, the present invention proposes a TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating and a preparation method and application thereof.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] A TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating, the raw materials are:

[0008] Graphene, multi-walled carbon nanotubes, hydrophobic titanium dioxide, and a binder;

[0009] Wherein, the mass ratio of the graphene to the multi-walled carbon nanotubes is 1:2;

[0010] The preparation process of the hydrophobic titanium dioxide is:

[0011] Adding nano titanium dioxide into a mixed solution consisting of deionized water, ammonia, ethanol and triethoxysilane; performing a secondary stirring treatment, and then vacuum drying to obtain the hydrophobic titanium dioxide;

[0012] The binder is PVDF, DMF, NMP and PDMS.

[0013] Beneficial effects: The present invention fully considers the dual requirements of the composite coating for photothermal performance and superhydrophobic performance, and simultaneously introduces two carbon-based materials with different structures into the superhydrophobic and durable anti-icing coating, namely, layered graphene (GPE) and cylindrical carbon nanotubes (MWCNTs), i.e., multi-walled carbon nanotubes, to give the coating excellent electrothermal and photothermal deicing effects and adjust the microstructure of the coating.

[0014] The reaction mechanism involved in the present invention is as follows: in terms of microstructure, TiO2, graphene and MWCNTs are intertwined in the coating to form a complex micro-nano structure. This structure can capture air and form cavitation, so that the contact area between water droplets and the coating surface is reduced, thereby achieving super-hydrophobicity. As an inorganic nanoparticle, TiO2 plays a role in increasing the surface roughness and providing photocatalytic properties in the coating. Its unique surface structure helps to form a super-hydrophobic surface, and can decompose organic matter under light conditions, thereby improving the self-cleaning ability of the coating;

[0015] Graphene has excellent electrical conductivity, thermal conductivity and mechanical strength. In the coating, graphene can form a continuous conductive network to improve the overall conductivity of the coating. At the same time, the two-dimensional structure of graphene helps to form a micro-nano structure, further enhancing the super-hydrophobicity of the coating.

[0016] MWCNTs have a high aspect ratio and excellent mechanical properties. In coatings, MWCNTs can enhance the mechanical properties and durability of coatings. They can also work synergistically with graphene to form a more stable micro-nanostructure, improving the superhydrophobicity and anti-icing properties of coatings.

[0017] In addition, in the process of preparing hydrophobic titanium dioxide, triethoxysilane (TEOS) undergoes hydrolysis and condensation reaction in the mixed solution to generate silanol groups (Si-OH). These silanol groups undergo condensation reaction with the hydroxyl Ti-OH on the surface of nano-titanium dioxide TiO2 to form chemical bonds. This chemical bonding allows the hydrophobic groups (such as methyl or ethyl) of triethoxysilane to cover the TiO2 surface, thereby achieving hydrophobic modification.

[0018] Preferably, the mass ratio of the graphene, multi-walled carbon nanotubes, hydrophobic titanium dioxide and binder is: 0.06:0.12:0.1:7.5.

[0019] Preferably, the D50 (D50 refers to the median diameter, that is, the median of 50% of the particle size distribution) of the graphene is 7-12 μm, and the aspect ratio is 9500; and / or the inner diameter of the multi-walled carbon nanotube is 5-12 nm, the outer diameter is 30-50 nm, and the length is 10-20 μm.

[0020] Beneficial effects: The present invention limits the D50 of graphene to the range of 7-12 μm, which can ensure the uniform distribution of graphene particles in the coating and avoid agglomeration or uneven dispersion caused by particles that are too large or too small. If the particles exceed this range, the problem of particles being too large or too small may occur. Particles that are too large may cause agglomerates to appear in the coating, reduce the uniformity and flatness of the coating, and affect the overall performance; although particles that are too small may contribute to the fineness of the coating, they may increase the viscosity of the coating, affect the construction performance, and are not conducive to the formation of a stable graphene network structure. If the diameter-to-thickness ratio is lower than the set value, the force between the graphene sheets may be weakened, making it difficult to form a stable network structure. The dispersibility of graphene in the coating will also deteriorate, and agglomerates are easily formed, affecting the overall performance of the coating.

[0021] If the inner diameter or outer diameter of the multi-walled carbon nanotube exceeds the range, two situations may occur. If the inner diameter is too small, the tube cavity is narrow, which is not conducive to improving the thermal and electrical conductivity; if the inner diameter is too large, the dispersion of the carbon nanotubes in the coating becomes poor, and it is easy to form agglomerates, affecting the uniformity and performance of the coating. As for the length, if it is too long, the dispersion of the carbon nanotubes in the coating will be poor and it is easy to form agglomerates; if it is too short, it will be difficult to form a stable network structure, affecting the performance of the coating.

[0022] Furthermore, the usage ratio of the nano titanium dioxide, deionized water, ammonia, ethanol and triethoxysilane is: 2g:20mL:2mL:90mL:1mL.

[0023] Furthermore, the secondary stirring treatment process is: first magnetic stirring at 1200r / min for 24h at 40°C, and then centrifugal stirring at 8000r / min for 10 minutes; and / or the vacuum drying condition is: vacuum drying at 60°C for 24h.

[0024] Optionally, the PDMS is composed of a PDMS component A and a PDMS curing agent B in a mass ratio of 10:1.

[0025] Further, the preparation process of the binder is:

[0026] The PVDF and NMP are mixed uniformly at a mass ratio of 0.5:8 to obtain a mixed solution 1;

[0027] The PDMS and DMF are mixed evenly at a mass ratio of 0.1:20 to obtain a mixed solution 2;

[0028] Then, the mixed solution 1 and the mixed solution 2 are evenly mixed in a mass ratio of 2:1 to obtain the adhesive. Beneficial effects: PDMS is usually insoluble in organic solvents, but under certain conditions, it can show certain solubility or dispersibility in DMF. The mixing here is to allow PDMS to be evenly dispersed in the solution. The mixing of PVDF and NMP is mainly based on the good solubility of PVDF in NMP. As an organic solvent, NMP can dissolve PVDF and increase its intermolecular distance, so that the PVDF molecules are gradually dispersed into NMP to form a solution. This dissolution and dispersion process contributes to the subsequent formation of the adhesive and the performance of its performance. Separate mixing can also ensure that each component achieves sufficient uniformity and stability before mixing, which helps to form an adhesive with better performance during subsequent mixing.

[0029] The second technical solution of the present invention:

[0030] A method for preparing a TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating comprises the following steps:

[0031] Adding hydrophobic nano-titanium dioxide, graphene and multi-walled carbon nanotubes into the binder, mixing and stirring to obtain a target solution;

[0032] The target solution is sprayed onto a substrate by one-step spraying, and then dried to obtain the TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating.

[0033] Preferably, the spraying step is:

[0034] The spray pot was controlled to make uniform horizontal motion along the axial direction of the substrate, the spraying time was 1 minute, and the number of spraying cycles was 5 times.

[0035] Furthermore, the spraying amount of the target solution on the substrate is 0.25 mL / cm 2 .

[0036] The third technical solution of the present invention:

[0037] The application of the TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating in anti-icing surface engineering.

[0038] Compared with the prior art, the present invention has the following advantages and technical effects:

[0039] The super-hydrophobic and durable anti-icing coating obtained by the preparation method of the present invention can be based on photothermal and electrothermal to meet the adaptability of wind turbine fan blades for all-weather anti-icing and de-icing, and has a lower adhesion strength of ice to the coating, the lowest of which is only 16±1.5 KPa.

[0040] The present invention adopts a one-step spraying method, which has the advantages of simplifying the process flow, reducing costs, improving uniformity and consistency, being suitable for substrates with complex shapes, easily controlling the coating thickness, improving production efficiency, being environmentally friendly and multifunctional, etc. These advantages make it an ideal choice for preparing functional coatings such as super-hydrophobic and durable anti-icing coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0042] Figure 1 The SEM images of the super-hydrophobic and durable anti-icing coating prepared in Example 1, wherein (a) is a morphology image of the substrate, (b) is a morphology image of the super-hydrophobic and durable anti-icing coating, and (c) is an overall morphology image of the substrate + super-hydrophobic and durable anti-icing coating;

[0043] Figure 2 Schematic diagram of the static water contact angle and rolling angle of the super-hydrophobic and durable anti-icing coating prepared in Example 1;

[0044] Figure 3 This is a self-cleaning effect diagram of the super-hydrophobic and durable anti-icing coating prepared in Example 1;

[0045] Figure 4 Deicing captured images of the substrate sample and the super-hydrophobic and durable anti-icing coating sample prepared in Example 1, wherein (a) is the room temperature deicing and photothermal deicing captured images of the substrate sample; (b) is the room temperature deicing and photothermal deicing captured images of the super-hydrophobic and durable anti-icing coating prepared in Example 1; (c) is the electrothermal deicing and photothermal and electrothermal combined deicing captured images of the coating sample prepared in Example 1;

[0046] Figure 5 Graph showing the change in adhesion between ice and the super-hydrophobic and durable anti-icing coating prepared in Example 1, and between ice and the substrate at different ambient temperatures. DETAILED DESCRIPTION

[0047] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0048] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0049] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0050] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0051] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0052] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.

[0053] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.

[0054] The raw materials used in the present invention are all purchased from the market.

[0055] The technical solution of the present invention is further illustrated by the following embodiments.

[0056] Example 1

[0057] A method for preparing a TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating comprises the following steps:

[0058] (1) Prepare an epoxy glass fiber board sample with a size of 50 mm × 50 mm × 0.3 mm, use a sandblasting device to sandblast the surface of the substrate sample, and keep the sandblasting time at 30 s to obtain a substrate with a surface roughness range of 0.8-1.5 μm. Then take it out, use anhydrous ethanol and deionized water to ultrasonically clean it, and dry it for use;

[0059] (2) Prepare materials: graphene (GPE, D50: 7-12 μm, diameter-to-thickness ratio: 9500), multi-walled carbon nanotubes (MWCNTs ≥ 95%, inner diameter: 5-12 nm, outer diameter: 30-50 nm, length: 10-20 μm), polyvinylidene fluoride (PVDF, Hsv900), ammonia, N, N-dimethylformamide (DMF, ≥ 99.8%), nano-titanium dioxide (99.5% metal base, 30 nm), triethoxysilane (> 97.0%), anhydrous ethanol (water ≤ 0.2%), N-methylpyridone (NMP, 98.0%), polydimethylsiloxane (PDMS);

[0060] (3) Using an electronic balance, PVDF, NMP, PDMS, and DMF were weighed (PVDF 0.5 g, NMP 8 g, PDMS 0.1 g, and DMF 20 g). PVDF and NMP were mixed and stirred at a magnetic speed of 1500 rpm for 30 minutes to obtain a mixed solution 1. PDMS and DMF were mixed and stirred at a speed of 1500 rpm for 30 minutes to obtain a mixed solution 2. The two mixed solutions were placed in cleaned beakers and stirred using a magnetic rotor for 30 minutes. The two mixed solutions were left to stand for use.

[0061] (4) The two mixed solutions obtained in step (3) were weighed using an electronic balance, 2.5 g (mixed solution 2) and 5 g (mixed solution 1), respectively, and mixed to obtain a mixed solution.

[0062] (5) 0.1 g of hydrophobic nano-titanium dioxide (F-TiO2) was added to the mixed solution of step 4, and then GPE / MWCNTs were added thereto at a mass ratio of 1:2 (wherein 0.06 g of graphene and 0.12 g of multi-walled carbon nanotubes), ultrasonically vibrated for 20 minutes, and stirred at room temperature of 50°C for 4 hours to obtain the target solution;

[0063] Among them, the preparation process of hydrophobic nano titanium dioxide is:

[0064] First, 2 g of nano-titanium dioxide was added to a mixed solution consisting of 20 mL of deionized water, 2 mL of ammonia, 90 mL of ethanol, and 1 mL of triethoxysilane;

[0065] Then, the mixture was magnetically stirred at 1200 r / min for 24 h at 40 °C, and then centrifugally stirred at 8000 r / min for 10 min;

[0066] Finally, the super-hydrophobic nano-titanium dioxide particles were obtained by vacuum drying at 60 °C for 24 h.

[0067] (6) Use a one-step spraying technique to spray 0.5 mL of the experimental coating solution onto the epoxy glass fiber board. The spraying time is 1 min and the number of spraying cycles is 5 times. In order to ensure uniform spraying of the sample, the spray bottle is controlled to move horizontally at a uniform speed along the axial direction of the sample, and the speed is always kept consistent. After drying at 100 °C for 1 hour, the sample is taken out to obtain a TiO2 / GPE / MWCNTs coating on the surface of the epoxy glass fiber board sample.

[0068] Effect verification

[0069] Related characterization and test methods:

[0070] (1) Surface 3D morphology features:

[0071] The surface morphology of the super-hydrophobic and durable anti-icing coating prepared in Example 1 was characterized by an optical microscope, and its surface roughness and 3D morphology were characterized by a non-contact optical profilometer.

[0072] (2) Microstructure characteristics of coating:

[0073] The surface microstructure of the super-hydrophobic and durable anti-icing coating prepared in Example 1 was characterized by using a JSM-6360LVSEM scanning electron microscope, with a scanning voltage of 20 kV and a working distance of 10 mm.

[0074] (3) Experimental steps for measuring static water contact angle:

[0075] The surface wettability of the super-hydrophobic and durable anti-icing coating prepared in Example 1 was tested using a fully automatic optical contact angle meter. The test solvent was deionized water, the volume of the test droplet was 5 μL, the release rate was 1 μL / s, and 5 positions were selected for each sample for testing, and the average value was calculated.

[0076] (4) Experimental steps for measuring freezing time of supercooled droplets:

[0077] The superhydrophobic and durable anti-icing coating prepared in Example 1 was measured for the freezing time of supercooled droplets in an environmental chamber at -10°C; a syringe (filled with deionized water) was prepared with a release rate of 0.2 mL / s and a test droplet volume of 1 mL. The prepared sample and the corresponding reference substrate were placed in the environmental chamber for precooling, and then a camera was prepared to drop deionized water onto the sample and simultaneously record the freezing of the supercooled droplets on the sample surface, completely recording the nucleation and freezing process of the entire droplet. Three positions were selected for each sample for testing, and the average freezing time was calculated.

[0078] (5) Coating self-cleaning performance test experiment:

[0079] The contact angle (CA) and sliding angle (SA) of the coating were measured 5 times with 5 μL of deionized water. The sputtering behavior of the coating was recorded with a camera and a fully automatic optical contact angle meter. The slope was covered with yellow quartz sand to simulate external pollutants, and deionized water was continuously dripped at a distance of about 10 cm from the coating. The residual state of quartz sand on the coating surface was observed to test the self-cleaning performance of the coating.

[0080] (6) Photothermal conversion performance test:

[0081] A xenon lamp (MICROSOLAR 300) was used to replicate natural sunlight. The substrate and the coated sample were placed parallel to the xenon lamp for about 20 cm and the light power density was set to irradiate the sample. At a solar intensity of 0.1 W / cm 2 The surface temperature of the sample was recorded, and then the light power density was set to 3 different levels (0.05 W / cm 2 , 0.1W / cm 2 and 0.15W / cm 2 ), study the surface temperature rise of samples under different light intensities. By setting three illumination angles of 30°, 60°, and 90°, the variation trend of sample surface temperature under different illumination angles is investigated. Here, the temperature detection of all samples is measured using an infrared thermometer.

[0082] (7) De-icing performance test:

[0083] First, 2 mL of liquid droplets were dropped on the surface of the coating sample and the substrate sample and frozen at -20 °C and 50 ± 5% RH (relative humidity) for 2 h to study the actual deicing ability of the coating. Then, the samples were taken out and placed upright to compare the deicing at room temperature (22 °C), photothermal deicing (0.1 W / cm 2 ), electric heating deicing (0.2W / cm 2 ), photothermal deicing (0.1W / cm 2 ) Combined electric heating deicing (0.2W / cm 2). In addition, the adhesion between ice and the coating is another important indicator. To this end, about 0.5 mL of deionized water was dropped onto the sample surface and placed in an environment of -10℃, -15℃, -20℃, and -25℃ for 4 hours at 50±5%RH. The maximum thrust of the ice drop was recorded using a push-pull force gauge, and the total contact area between the ice and the surface was determined using contour analysis.

[0084] Figure 1 This is a SEM image of the super-hydrophobic and durable anti-icing coating prepared in Example 1; wherein, Figure 1 (a) shows the morphological characteristics of the substrate. As can be seen from the figure, the surface of the substrate is slightly convex and has a characteristic yellow color, which is conducive to the combination of the coating and the substrate; the surface of the coating sample is dense and uniform, without pores; and Figure 1 Middle (c) shows that the composite coating thickness is only 20 μm;

[0085] Figure 1 (b) shows that the surface morphology of the super-hydrophobic and durable anti-icing coating has a coral-like micro-nanostructure, in which TiO2 nanospheres with an average size of 20-30nm are aggregated and adhered to a micro-scale structural matrix composed of graphene and carbon nanotubes. The distribution positions of the four elements C, Ti, O, and F shown in the EDS spectrum (as shown in Table 1) correspond to the SEM image. Since the heat treatment process of the coating completely evaporates NMP and DMF as solvents, the nitrogen content is 0.

[0086] Table 1

[0087]

[0088] Figure 2 The static water contact angle and sliding angle of the super-hydrophobic and durable anti-icing coating prepared in Example 1 are as follows: CA is 167° and SA is 4°.

[0089] Figure 3 This is a self-cleaning effect diagram of the super-hydrophobic and durable anti-icing coating prepared in Example 1; Figure 3 It is shown in the self-cleaning experiment that due to the low adhesion of water droplets on the coating surface and the adhesion of pollutants on the surface is smaller than the adhesion between water and the coating, the water droplets continue to fall and roll down quickly, taking away all the quartz sand on the surface without leaving any residue, further verifying that the TiO2 / GPE / MWCNTs superhydrophobic and durable anti-icing coating has excellent superhydrophobicity.

[0090] The photothermal performance of the super-hydrophobic composite coating was studied by simulating the changes in actual solar illumination conditions. 2Under the light intensity of , the surface temperature of the composite coating rises rapidly and reaches an equilibrium peak temperature of about 68.4℃ after about 81s of sunlight exposure. After that, the surface temperature remains at this peak temperature and no longer changes with the extension of irradiation time. Under the same irradiation time, the equilibrium peak temperature reached on the substrate surface is only 39.9℃.

[0091] Considering that the light intensity in the natural environment is not fixed, the coating sample and the substrate were studied at 0.05W / cm 2 , 0.10W / cm 2 and 0.15W / cm 2 Temperature rise behavior under the sun. The temperature rise of the super-hydrophobic and durable anti-icing coating has a significant dependence on light intensity. Under the same illumination time conditions, the peak temperature of the surface of the super-hydrophobic and durable anti-icing coating (Example 1) increases from 0.05W / cm 2 56.6℃ under the sun significantly increased to 0.15W / cm 2 Under the sun, the surface temperature of the substrate does not change significantly with the light intensity. Under the irradiation of three light intensities, the surface temperature of the substrate is in a narrow range of 33.6-40.7°C. Obviously, the composite coating of the present invention is 2 The surface temperature obtained under weak solar light conditions is significantly higher than the peak temperature of the substrate under strong light conditions, indicating that the superhydrophobic and durable anti-icing coating has extremely high photothermal properties.

[0092] The present invention is set under no external conditions (i.e. room temperature), photothermal (0.1W / cm 2 ), electric heating (0.2W / cm 2 The deicing ability of the superhydrophobic coating was evaluated by studying the melting process of ice condensed on the coating under the conditions of light, heat and electric heat. For comparison, the melting process of ice condensed on the substrate under room temperature and light conditions was also carried out. The time required for ice to slide off the surface is the standard for the end of deicing here. Figure 4 As shown in the figure, the ice on the substrate began to melt at room temperature at 168s and completely melted into liquid at 933s. The ice on the substrate did not slide off during the melting process. 2 ), the ice on the substrate began to melt at 151s and completely melted into liquid at 426s, which was 507s shorter than the time at room temperature. It can be seen that the melting of ice on the substrate made a big difference. At room temperature, the ice on the coating began to melt at 87s and began to fall off within 182s. Compared with the ice on the substrate surface under light conditions, the melting time was shortened by 65.5%. When the ice on the coating was subjected to simulated light of 0.1W / cm 2When the ice is exposed to the sun, it begins to melt earlier, starts to melt and slide down at 33s, and finally melts into water completely within 134s, completing the slide. There are no droplets on the surface because the ice beads absorb the sun's heat from top to bottom. The photothermal deicing efficiency of ice is 26.4% higher than that of normal temperature deicing. When the electric power density is 0.2W / cm 2 When the ice was heated to 0.1 W / cm2, the ice on the coating began to melt and slide within 30 seconds, and completely slid off the surface within 64 seconds. At this time, the ice beads had not yet completely melted into liquid. This is because the bottom-up heat transfer method in the electrothermal deicing melts the interface between the ice and the coating, producing a lubricating layer. At the same time, the micro-nanostructure on the coating surface makes it slide faster. In addition, when the ice on the coating is heated to 0.1 W / cm2 by photothermal and electrothermal (photothermal is 0.1 W / cm2), the ice on the coating is completely melted and completely slid off the surface within 64 seconds. 2 , electric heating is 0.2W / cm 2 ) in just 18 seconds, and the ice beads completely slide off the coating surface in 51 seconds, which is 61.9% faster than pure light-thermal deicing and 20.3% faster than electric deicing.

[0093] The adhesion strength of ice is an important indicator for evaluating the deicing ability of coatings. Here, the adhesion strength of the super hydrophobic and durable anti-icing coating prepared in Example 1 and the ice formed on the substrate was tested at -10°C, -15°C, -20°C and -25°C respectively. Figure 5 As shown, in the range of 250-380KPa, the adhesion strength of ice formed on the surface of the substrate at four different temperatures is basically at a similar strength level; for the superhydrophobic and durable anti-icing coating, the adhesion strength of ice formed on the surface is significantly lower than that of the substrate, and the adhesion strength of ice on the superhydrophobic and durable anti-icing coating shows a slight upward trend with the decrease of freezing temperature. At -20℃, the adhesion strength of ice to the coating is 16±1.5KPa, but this is also lower than the adhesion strength of ice to the substrate.

[0094] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating, characterized in that: The raw materials are: Graphene, multi-walled carbon nanotubes, hydrophobic titanium dioxide, and a binder; Wherein, the mass ratio of the graphene to the multi-walled carbon nanotubes is 1:2; The preparation process of the hydrophobic titanium dioxide is: Adding nano titanium dioxide into a mixed solution consisting of deionized water, ammonia, ethanol and triethoxysilane; performing a secondary stirring treatment, and then vacuum drying to obtain the hydrophobic titanium dioxide; The binder is PVDF, DMF, NMP and PDMS.

2. A TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating according to claim 1, characterized in that: The mass ratio of the graphene, multi-walled carbon nanotubes, hydrophobic titanium dioxide and binder is 0.06:0.12:0.1:7.

5.

3. A TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating according to claim 1, characterized in that: The graphene has a D50 of 7-12 μm and an aspect ratio of 9500; and / or The multi-walled carbon nanotube has an inner diameter of 5-12 nm, an outer diameter of 30-50 nm, and a length of 10-20 μm.

4. The TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating according to claim 1, characterized in that: The dosage ratio of the nano titanium dioxide, deionized water, ammonia, ethanol and triethoxysilane is: 2g: 20mL: 2mL: 90mL: 1mL.

5. The TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating according to claim 1, characterized in that: The preparation process of the binder is as follows: The PVDF and NMP are mixed uniformly at a mass ratio of 0.5:8 to obtain a mixed solution 1; The PDMS and DMF are mixed evenly at a mass ratio of 0.1:20 to obtain a mixed solution 2; Then, the mixed solution 1 and the mixed solution 2 are uniformly mixed in a mass ratio of 2:1 to obtain the binder.

6. A method for preparing a TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating, characterized in that: The following steps are involved: Adding hydrophobic nano-titanium dioxide, graphene and multi-walled carbon nanotubes into the binder, mixing and stirring to obtain a target solution; The target solution is sprayed onto a substrate by one-step spraying, and then dried to obtain the TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating according to any one of claims 1 to 5.

7. The method for preparing a TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating according to claim 6, characterized in that: The spraying amount of the target solution on the substrate is 0.25 mL / cm 2 .

8. Application of the TiO2 / GPE / MWCNTs super-hydrophobic and durable anti-icing coating as described in any one of claims 1 to 5 in anti-icing surface engineering.

Citation Information

Patent Citations

  • Super-hydrophobic icing prevention coating with active photothermal deicing function, coating layer, preparation method of coating and application of coating

    CN109486269A

  • Preparation method of fluoride-free wear-resistant super-hydrophobic anti-icing coatinglayer with photothermal effect

    CN114058227A

Cited By

  • Biphase hybrid anti-icing coating as well as preparation method and application thereof

    CN121975431A

  • A dual-phase hybrid anti-icing coating and its preparation method and application

    CN121975431B